Analisis Burnout Pada Karyawan Dinas Badan Pusat Statistik - Anggari, Dewi Patimah; Fadli, Uus Muhammad Darul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine burnout among Central Statistics Agency employees. The research method used is a qualitative method, qualitative data was obtained through in-depth interviews with BPS employees, the community received statistical information from the Karawang Central Statistics Agency (BPS). BPS employees are highly dependent on their performance, which has a direct impact on monitoring information and public services. However, the stressful work environment at BPS Karawang often leads to burnout, chronic stress conditions, and an imbalance between personal and work life. Burnout reduces organizational and individual performance. The aim of this research is to identify the causes of fatigue at BPS Karawang, effective stress management techniques, and prevention strategies. This research is expected to provide management with knowledge about how to create a healthy and productive work environment, improve employee health, and maintain organizational efficiency in the face of rapid social and economic change.